Promoted photocarriers separation by straining in 2D/2D van der Waals heterostructures for high-efficiency visible-light photocatalysis. (January 2022) - Wang, Yong; Zeng, Chengxin; Zhang, Yu; Su, Ran; Yang, Dingyi; Wang, Zhaokun; Wu, Yizhang; Pan, Hongzhe; Zhu, Weidong; Hu, Wen; Liu, Hong; Yang, Rusen
Abstract: Atomically thin 2D carbon-nitride-based Van der Waals heterostructures (vdWHs) are emerging and promising materials for visible-light-driven photocatalysis. However, a large potential barrier between the heterointerfaces of vdWHs prevents photogenerated carriers from being transported, which further limits their practical applications. Here, we report that the strain promotes photocarriers separation in 2D/2D vdWHs for visible-light photocatalysis. The vdWHs assembled by atomically thin carbon nitride sheets (CNs) and molybdenum disulphide (MoS2 ) are used as an experimental prototype. Experimental results along with density functional theory (DFT) work show that the electric field caused by straining facilitates the separation of photogenerated electron-hole pairs and improves the transport of photogenerated carriers. Consequently, the photocatalytic activities of CNs/MoS2 vdWHs were significantly improved in terms of photocatalytic hydrogen evolution and photodegradation of Rhodamine B under visible-light illumination and ultrasonic irradiation. This study opens the gate to vdWHs-based high-performance photocatalysis. Graphical abstract: Promoted photocarriers separation by straining in 2D/2D vdWHs for visible-light photocatalysis is reported. The photocatalyst based on this material shows a much superior photocatalytic activity under visible-light and ultrasonic irradiation. Image 1 Highlights: Promoted photocarriers separation by straining in 2D/2D vdWHs is reported. This strategy can dramatically promote photocarrier separation in 2D/2D vdWHs. The photocatalyst based on this material shows a much superior photocatalytic activity.